Investigating How Students Transfer a Source Text into Speech through Lesson Study - Ilknur Bayram; Cisem Altug; Firdevs Pelin Dereli; Gokhan Yildiz; Yakup Uzun (European Scientific Journal, ESJ, 2017)
This study was designed to explore how students enrolled at the English Academic Presentation Skills and English for Logistics Courses transfer a piece of written text into speech. Designed as a Lesson Study Project, this study was carried out during the 2016-17 Fall Semester by five teachers with the participation of 68 students from three different departments and four different classes. Data in this qualitative case study was gathered through four research lessons, classroom observations, student interviews and analysis of student work. Findings of the study revealed that students tend to make changes in a written text in five different ways to be able to present it orally. These changes fall under the headings of organizational changes, sentence level changes, summarizing the text, using key details and use of transitions.